The sounds of digital music as a resource for english teaching learning process with the third year undergraduate students at ―provincia de Cotopaxi‖ high school during the academic cycle march - august 2014 - Chicaiza Ganchala, Karla Alejandra (2015)
Learning English as a Foreign Language is a fundamental aspect into education. That is why in order to acquire this important language; it is needed to develop the listening, speaking, reading and writing skills. Being listening and the pronunciation the most difficult skills to develop in the teaching learning process of this language. This thesis work is directed to third year undergraduate students from Provincia de Cotopaxi High School. This work has as principal aim to improve the listening skill and pronunciation through the application of songs as didactic resources. For the development of this work, it was used the descriptive method in order to determine the theoretical fundaments. The poblation of this investigation were a group of 90 students, five authorities and six English teachers, which were applied interviews and surveys respectively....